THE ROLE OF WORK MOTIVATION AS A MEDIATING VARIABLE IN THE INFLUENCE OF WORK ORIENTATION AND COMPENSATION ON EMPLOYEE PERFORMANCE IN THE ERA OF DIGITALIZATION AND THE USE OF AI TECHNOLOGY AT MATA MATA HOSPITAL - Ni Kadek Ika Darmayanti; Nilna Muna (RADJA PUBLIKA, 2026)
The development of the era of digitalization and the use of artificial intelligence (AI) technology requires organizations, including hospitals, to have adaptive and high-performance human resources. Employee performance is influenced by various factors, including job orientation, compensation, and work motivation. This study aims to analyze the influence of work orientation and compensation on employee performance with work motivation as a mediating variable at Ramata Eye Hospital in the era of digitalization and the use of AI technology. This study uses a quantitative approach with a survey method. The population in this study is all employees of Mata Eye Hospital, with a sample of 136 respondents determined using saturated sampling techniques. Data collection was carried out through a questionnaire measured using the Likert scale. Data analysis was carried out using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The results of the study show that work orientation and compensation have a positive and significant effect on employee performance. In addition, job orientation and compensation also have a positive and significant effect on work motivation. Work motivation has been shown to have a positive and significant effect on employee performance and acts as a partial mediating variable in the relationship between work orientation and compensation for employee performance. These findings show that improving employee performance depends not only on compensation and job orientation, but also on strengthening work motivation, especially in the face of the demands of technological adaptation and the digitalization of healthcare services. This research is expected to make a theoretical contribution to the development of human resource management as well as a practical contribution to the management of Ramata Eye Hospital in formulating strategies to improve employee performance in a sustainable manner.